ALKALINE ALUMINOSILICATE COATING TO PROTECT CONCRETE AGAINST THE TRANSPORT OF CL--IONS UNDER PERIODICAL CYCLES OF WETTING/DRYING (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
To ensure the durability of constructions is current world tendency of building industry. It’s well known that the periodical effect of chlorine-containing aqueous environment and carbonation under the action of atmospheric carbonic gas causes the most risk of the corrosion of steel reinforcement. The carbonation contributes toward releasing the bound Cl--ions adsorbed on hydration products. The advanced transport of Cl--ions ensures the corrosion of steel reinforcement. Thus, the mean to prevent the transport of aggressive ions in concrete from aggressive environment with combination of exposure classes XD3 and XC4 is actual for investigations. The coatings based on alkaline aluminosilicate binders were proposed for protection of reinforced concrete against the ingress of aggressive ions because of their well-known capability to ones bind in the zeolite-like phases.The aim of this research was to determine the effectiveness of coating based on alkaline aluminosilicate binder of the composition (0.2K2O+0.8Na2O)·4.5SiO2·Al2O3·nH2O as protection of reinforced concrete from transport of Cl-, CO32--ions under periodical cycles of wetting/drying. The evaluation of protective properties of proposed coating in real operating conditions under cyclic drying-wetting in chlorine-containing aqueous environment was determined using the author’s methodology.Total protection of concrete after 90 cycles of drying-wetting in a 5 % solution of NaCl in the absence of traces of Cl--ions transport can be ensured by 3 mm of the coating. High protective properties of the coating were confirmed by the retention of its adhesion as well as high corrosion resistance of coated concrete under the action of specified aggressive environment. High protective properties of the coating are caused by binding Cl‑ and CO32- ions in the water-resistant zeolite-like matrices.
Keywords: alkali-activated slag concrete; sodium nitrate; carbonization; sea water; pore structure.